A Catalytic, Oxidative Synthesis of Olivetol, Methyl Olivetolate and Orthogonally Protected Methyl Ether Derivatives - Hurem, David; Macphail, Benjamin J.; Carlini, Rina; Lewis, Jason; McNulty, James (SynOpen, 2021)
Olivetol, methyl olivetolate and a series of orthogonally protected methyl ether derivatives were synthesized from commonly available precursors using an atom-economical, catalytic oxidative aromatization process.
Keywords: olivetol; olivetolic acid; aromatization; catalysis; oxidation; polyketide; meroterpenoid